Effects of salinity and water quality parameters on the breeding and larva rearing of black molly Poecilia sphenops in laboratory condition - Wan Hassan, Wan Nurul Husna; Christianus, Annie; Che Cob, Zaidi; Abd. Ghaffar, Mazlan; Das, Simon Kumar (Bioflux, 2014)
A study was conducted to determine the effects of salinities (0, 3 and 6 PSU) and other water quality parameters on the breeding and larva rearing of black molly Poecilia sphenops (Valenciennes 1846) under laboratory condition. Each treatment was carried out in triplicates. Results showed that water salinity of 6 PSU represented the highest breeding success compared to salinities of 0 and 3 PSU. Nevertheless, no significant differences (p > 0.05) were observed at these three salinities for fry production in captivity. Moreover no significant differences were observed in weight increment when salinity raised from 3 to 6 PSU, however, these two treatments differed significantly when compared with 0 PSU. The survival rate was not significantly varied in comparison with 0 PSU. The highest total length increment was found at water salinity of 6 PSU followed by 0 and 3 PSU. Results on water quality parameters denoted no significant differences (p > 0.05) for all treatments except on ammonia (NH3) rates. The highest ammonia level was found at 0 PSU followed by 3 and 6 PSU. The findings of the present study suggested to culture black molly (P. sphenops) in a slight saline condition from 3 to 6 PSU.